Pengaruh Bopo Dan Net Interest Margin Terhadap Return On Asset PT Bank Danamon TBK Periode 2014-2024 - Abimanyu Trias Nugroho; Intan Sari Budhiarjo (Journal of Innovative and Creativity, 2026)
This study aims to determine the effect of Operating Costs, Operating Income, and Net Interest Margin on Return on Assets at PT Bank Danamon Tbk for the 2014-2024 period. The method used is a quantitative method. The sample used in this study is the financial statements of PT Bank Danamon Tbk for the 2014-2024 period. Data analysis used is a classical assumption test, regression analysis, Coefficient of Determination that the Coefficient of Determination (R Square) is 0.754 or 75.4% and hypothesis testing. The results of this study are in the hypothesis test stating that BOPO has no effect on Return on Assets with a t count of 1.788 <t table 2.306 and a sig value of 0.112> 0.05. While on the Net Interest Margin variable, the hypothesis test shows that there is an influence on the Return on Assets variable with a t count of 2.452> t table 2.306. and the sig value is 0.040, and the simultaneous test results state that BOPO and NIM have a significant effect on ROA with the results of F count > F table, where the amount is (12.238 > 4.46) and the sig value is 0.004 < 0.05.